Polityka kursu walutowego w Polsce w okresie transformacji systemowej w świetle aspiracji do członkostwa w strefie euro - Biegun, Krzysztof (Exchange rate policy in Poland in the transition period in the background of EMU membership aspirations, 2006)
The first part of this article includes a review of modern exchange rate mechanisms with their short characteristics and presents theoretical introduction to the problem. The second part presents exchange rale policy in Poland in the transition period in the context of pursuance to course convergence criterion fullfilment.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 298-306